Indion 190 resin: Reusable catalyst for the synthesis of quinoxalines and pyrido-pyrazines at ambient temperature - Meshram, Gangadhar Asaram; Deshpande, Shruti Shashank; Vala, Vipul Amratlal; Wagh, Pramod Arun (European Journal of Chemistry, 2013)
An efficient method for synthesis of quinoxalines and substituted pyrido-pyrazines has been developed from different 1,2-dicarbonyl compounds and substituted 1,2-diamines using Indion 190 resin as a solid acid catalyst. Ambient reaction conditions, high product yield and reusability of the catalyst with minimal loading are the salient features of the present protocol.